Effect of magnesium lactate dihydrate and calcium lactate monohydrate on 20-km cycling time trial performance - Peveler, W. W.; Palmer, T. G. (The Journal of Strength and Conditioning Research, 2012)
Manufacturers of supplements containing magnesium lactate dihydrate and calcium lactate monohydrate claim improved athletic performance. Although energy can be produced through the lactate shuttle system, there is limited evidence to suggest that substantial quantities are available for human movement during exercise. The purpose of this study was to evaluate the effectiveness of lactate as a performance-enhancing substance. Nine recreational to competitive cyclists (VO2max = 52.46 ± 11.8) completed 3 simulated 20-km time trials conducted on a Velotron. The first trial was used as a familiarization trial, and the last 2 trials were counterbalanced ergogenic aid/placebo trials. To eliminate the possibility of bias, the study was conducted double blind. Dependent measures (time, mean power, heart rate [HR], and ratings of perceived exertion) for the 3 trials were compared using repeated measures analysis of variance (p = 0.05). There were no significant differences between placebo and ergogenic aid in measures of time (38.78 ± 5.87 minutes vs. 39.07 ± 6.00 minutes; p = 0.212), mean power (236.40 ± 74.8 W vs. 232.81 ± 76.12 W; p = 0.342), and HR (167.36 ± 10.11 minutes vs. 163.70 ± 13.07 minutes; p = 0.092). Ratings of perceived exertion for the placebo trial were significantly higher in relation to the ergogenic aid trial (15.97 ± 0.72 vs. 15.70 ± 0.85; p = 0.039). Although not significant, times during the placebo trials were faster in relation to the ergogenic aid trials. Ratings of perceived exertion were significantly higher in the placebo trials, which could reflect the trend toward faster times. Supplementation of magnesium lactate dihydrate and calcium lactate monohydrate does not appear to significantly improve times during a simulated 20-km time trial and therefore should not be recommended for use as an ergogenic aid.